Integration of the Qur'anic Property Rights Concept in the Development of Productive Wakaf: A Thematic Interpretation Approach (Maudhu'i) - Farida Aprianti; Achmad Abubakar; Muhsin Mahfuz; Muhammad Rusdin (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2026)
The purpose of this study is to examine the concept of property rights in the Qur'an and its relevance to the development of productive waqf. This study uses a thematic interpretation approach with the following steps: compiling Qur'anic verses related to property rights and asset management; analyzing linguistic meanings, contexts, and correlations between verses; and synthesizing Qur'anic values that can be implemented in the management of productive waqf. The factual finding is that the suboptimal nature of productive waqf, caused by low literacy and inadequate appreciation of the Qur'anic right of ownership, hinders waqf management. As a result, this hinders the fulfillment of social responsibilities, because the success of waqf requires understanding and dedication to religious and economic interests. The results of the study show that ownership rights in the view of the Qur'an are amanah (trust ownership), not absolute ownership, and must be oriented towards social functions. Qur'anic values such as amanah, distributive justice, and sustainability of benefits are the basic principles for the development of productive waqf that is fair and sustainable. This research contributes to strengthening the normative and theological foundations for productive waqf practices in the modern era, as well as offering a framework for integrating Qur'anic values into the management of community assets in accordance with maqāṣid al-syarī‘ah.